Simbiosis entre ciudad y poeta: Cuenca y Federico Muelas - Carrascosa Ortega, Marcial (Ángulo Recto. Revista de estudios sobre la ciudad como espacio plural, 2009)
The attachment between a poet and a city is a normal resource in literature since the ancient times, but there are few cases so outstanding as the one between Federico Muelas and Cuenca. After a small review to his life and literary production, I will try ti show the after mentiones symbiosis –which sometimes reach the absolute literacy– through some texts from the poet. In the same way that he sings to Cuenca's famous rocks, its rivers and riversides or to its emblematic monuments, he does it too to those forgotten people and places from Cuenca's land that remain unnoticed. Let never forget that Muelas was born in, with and for Cuenca.
Keywords: Cuenca; Federico Muelas; Hanging Houses; Rivers; Stone; Defile; Black poplar; Silence